The Procedures in English-Indonesian Translation of Islamic Terms - Frihatmawati, Rizky; Yuskar, Bobby Octavia; Yastanti, Unpris; Nurmalia, Lia (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
When translating a message, a translator needs to identify the most equivalent natural expression in Target Language (TL). Nevertheless, it is not always feasible to discover the corresponding translation for culturally specific text. The translators frequently need various procedures to accomplish the translation tasks. This study examines the procedures used in translating Islamic terms and the most common procedures used by translators in the book